Vues sur « mon corps troublé·e·s » – recherches-frictions - Claire Gauzente (Glad!)
This text explores several ways to go beyond, displace, disturb the binarized matrix of masculine/feminine genders for a more fluid vision of the existence of the human animal. It traces a day of research-frictions mixing academic and artistic research.